2019
DOI: 10.1029/2019jd030380
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Ammonia Concentrations Across New York State

Abstract: Ammonia (NH3) was monitored at four locations (two urban and two rural) across New York State from April 2016 to October 2017 using active and passive systems. The two rural sites were Pinnacle State Park (PIN) and the Village of Potsdam, and the two urban sites were the City of Rochester and Queens College in New York City. Active and passive concentrations were well correlated across all sites (r2 = 0.866), but the active systems measured 6.2% higher NH3 concentrations. The mean (±SD) NH3 concentrations meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 62 publications
3
17
1
Order By: Relevance
“…The high autumn ammonia concentrations were mostly likely due to low rainfall, which did not dilute or leach nitrogen from the soil slurry in the farming regions [58]. In addition, the increased use of fertilizers [59] and manure processing in the farm fields [6,17] during this time also likely resulted in a high ammonia concentration. Studies have also shown that the daily emission rate of ammonia is highest in the autumnwinter period, due to more pig fattening at this time, and that agricultural floors with daily manure removal have significantly lower emissions than concrete agricultural floors [60].…”
Section: Seasonal Variation In Ammonia Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The high autumn ammonia concentrations were mostly likely due to low rainfall, which did not dilute or leach nitrogen from the soil slurry in the farming regions [58]. In addition, the increased use of fertilizers [59] and manure processing in the farm fields [6,17] during this time also likely resulted in a high ammonia concentration. Studies have also shown that the daily emission rate of ammonia is highest in the autumnwinter period, due to more pig fattening at this time, and that agricultural floors with daily manure removal have significantly lower emissions than concrete agricultural floors [60].…”
Section: Seasonal Variation In Ammonia Concentrationmentioning
confidence: 99%
“…Therefore, Atmosphere 2021, 12, 1607 2 of 19 animal husbandry and its large-scale industrialization are significant sources of industrial emissions of ammonia [13]. Vehicle and agricultural emissions significantly contribute to ammonia pollution in major urban areas [14][15][16][17]. Ammonia also plays a primary role in the deterioration of atmospheric visibility and the deposition of nitrogen in the atmosphere [18].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 also shows observational results of atmospheric NH 3 from some other countries. The NH 3 concentrations in the USA (Edgerton et al, 2007;Nowak et al, 2006;Zhou et al, 2019), Scotland (Burkhardt et al, 1998), Canada (Hu et al, 2014), Japan (Osada et al, 2019), and Germany (Vogt et al, 2005) were 0.23-13, 1.6-2.3, 0.1-4, 4.1, and 5.2 ppb, respectively. These values are considerably lower than those in Beijing.…”
Section: Overall Variations In the Nh 3 Mixing Ratiosmentioning
confidence: 94%
“…Ammonia is a typical species out of agricultural emission (e.g. Misselbrook et al, 2000;Kirchmann et al, 1998;Zhou et al, 2019). Some Bris also present in the sea salt fraction of the aerosol.…”
Section: Accepted Manuscriptmentioning
confidence: 99%